Tinjauan Yuridis Terhadap Perampasan Aset-Aset Terpidana Korupsi di Indonesia - Yulianda, Premita; ', Firdaus; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Confiscation of assets convicted of corruption in Indonesia, still be the pros and cons. For those who are pro, rightfully convicted assets derived from corruption, it must be cleaned and should be taken quickly before the suspect or defendant may disguise the proceeds of crime and the exclusion of one of the statutory objectives, namely justice. Because considering the number who engage in corruption in Indonesia and corruption is an extraordinary crime. While they are cons, institutions authorized to plunder not see the rights of the suspect or the accused. The purpose of this study, to determine the expropriation of assets settings convicted of corruption in Indonesia, to know the state may seize suspected assets acquired prior to the occurrence of corruption, and to determine the mechanism of execution against the assets of the accused.The purpose of this minithesis, namely: First, to determine the implementation of environmental criminal enforcement by the Directorate of Criminal Investigation Special Riau Police against the perpetrators of forest and land fires. Second, to determine the constraints faced by the Directorate of Criminal Investigation Special Riau Police in environmental criminal enforcement against perpetrators of forest and land fires, and third, to find out the efforts made by the Special Criminal Investigation Directorate Riau Police to overcome obstacles in the enforcement of criminal law environment against the perpetrators of forest and land fires. This type of research is classified in legal studies is defined sociological look at the effectiveness of the law in force to see the correlation between the legal community.Expropriation of assets settings convicted of corruption provided for in Article 37 paragraph (2) and Article 38 paragraph (2) pursuant to Act No. 31 of 1999 as amended into Law No. 20 of 2001 on Corruption Eradication. Can be seen, that the lack of effective and inefficiency agencies duly authorized to that is to seize assets produced legally. Suggestions author, the first institutions authorized to plunder should really pay attention to the rights of the suspect/defendant, second, Law on Combating Crime Asset fast soon passed, so as not to create a dilemma for the authorities to carry out their duties, and the third, assets that are evident from the crime committed to restore the loss of the country's economy should be described anywhere result of crime assets are allocated.Keywords: Review-juridical-Deprivation-convict Assets-Corruption